The Impact of Entrepreneurial Business Passion of the Conventional Culinary SMESs to Sustain Through a Decade - Mhd. Andi Rasyid; Dian Inda Sari; Zahratu Diniyah (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This study investigated the impact between business passions of conventional culinary SMEs to their ability to sustain their business through a decade, in the city of Medan, Indonesia. They do not use technology and less innovation. They face dynamic and competitive environment especially during the Covid-19 Pandemic. They can even create jobs for others, reduce unemployment in their local area and also cut the poverty. In the fact, being entrepreneur is not easy as it seems. The culinary business comes and goes. This study used a questionnaire approach with a Linkert’s scale to test four indicator of business passion. Data tabulation was then processed using SEM with Lisrel. The results indicated that passion for the business has a direct impact to the conventional culinary SMEs respondents to sustain through a decade. This study suggests to the startups to have strong basic in their business, know what they do, make and have business passion. Making the business of tomorrow, business to remain existing and to remain successful in the future and must continue beyond the lifetime of the individual or of the generation to be capable of producing its contributions to economy and to society.